Using intranasal dexmedetomidine with buccal midazolam for magnetic resonance imaging sedation in children: A single-arm prospective interventional study - Li, Bi Lian; Luo, Hao; Huang, Jun Xiang; Zhang, Huan Huan; Paquin, Joanna R.; Yuen, Vivian M.; Song, Xing Rong (Frontiers in Pediatrics, 2022)
Objective: Although numerous intravenous sedative regimens have been documented, the ideal non-parenteral sedation regimen for magnetic resonance imaging (MRI) has not been determined. This prospective, interventional study aimed to investigate the efficacy and safety of buccal midazolam in combination with intranasal dexmedetomidine in children undergoing MRI. Methods: Children between 1 month and 10 years old requiring sedation for MRI examination were recruited to receive buccal midazolam 0.2 mg·kg−1 with intranasal dexmedetomidine 3 μg·kg−1. The primary outcome was successful sedation following the administration of the initial sedation regimens and the completion of the MRI examination. Results: Sedation with dexmedetomidine–midazolam was administered to 530 children. The successful sedation rate was 95.3% (95% confidence interval: 93.5–97.1%) with the initial sedation regimens and 97.7% (95% confidence interval: 96.5–99%) with a rescue dose of 2 μg·kg−1 intranasal dexmedetomidine. The median sedation onset time was 10 min, and a significant rising trend was observed in the onset time concerning age (R=0.2491, P < 0.001).The wake-up and discharge times significantly correlated with the duration of the procedure (R = 0.323, P < 0.001 vs R = 0.325, P < 0.001). No oxygen deficiency nor need for intervention due to cardiovascular instability was observed in any of the patients. History of a prior failed sedation was considered a statistically significant risk factor for failed sedation in the multivariate logistic regression model [odds ratio = 4.71 (95% confidence interval: 1.24–17.9), P = 0.023]. Conclusions: In MRI examinations, the addition of buccal midazolam to intranasal dexmedetomidine is associated with a high success rate and a good safety profile. This non-parenteral sedation paradigm can be a feasible and convenient option for short-time MRI in children between 1 month and 10 years.